A Glance of the Free Trade Agreement between Mexico and the European Union - Moises Marcos (European Regional Science Association (ERSA), 2003)
Mexico has had a notable trade performance in the last years as result of a process of economic liberalisation and internal structural reforms that started in the mid-1980s and consolidated in the 1990s by establishing a network of free trade agreements. The FTA between the European Union and Mexico is a consequence of many advantages, among others to open up a bigger markets, same legal footing as their competitors and new potential investments. The liberalisation is phased until 2007. Mexico has had a big jump in exports through NAFTA, and nowadays has a preferential access to the world's largest market, the EU. In addition, Mexico offers better conditions for investment because the work force and the private sector during the past 8 years (since NAFTA) have learned to compete efficiently against the American and Canadian firms. Actually, the free trades agreements have enabled to obtain gains from globalisation and market diversification through regional and bilateral negotiations being a powerful instrument for Mexico's economic growth and development. In conclusion, the new free trade agreement instead of dispiriting the distribution of income will promote (in the long-term) equality for the Mexicans, because of the productivity and the access to new opportunities
Keywords: 330